Advances in Nurses’ Pain Management Practices: The Case of Long-Term Care - Rojaye, Justin Oluwasegun (KHD-Production, 2024)
The most common medical issue that elderly people face in a long-term care facility is pain. Nurses play an important role in assisting residents with pain management. This study looked at nurses' pain management practices in long-term care facilities. This study took place at a long-term care facility in Ontario, Canada, a 160-bed nursing home for the elderly that offers a variety of nursing and medical care services. A one-hour semi-structured focus group interview was conducted. The population of this study included 45 nurses. Using a purposive sampling strategy, the researcher selected a sample of 25 nurses. To identify recurring issues, the data was reviewed using qualitative data analysis. This study revealed the importance of identifying and overcoming barriers to effective pain management and reinforcing good practices in long-term care homes; better pain management practises are required to manage pain in a long-term care home. This study demonstrated the significance of identifying and overcoming barriers to effective pain management and reinforcing best practices in long-term care homes. As a result, improved pain management practises are required to manage pain in a long-term care home effectively. The overall benefits of pain management practice in long-term care homes increase nurses' clinical knowledge in the care of nursing home residents.